The effectiveness of station market development on state land managed by pt. Kereta api Indonesia (Research, Society and Development, 2022)
The land used for the construction of the railway infrastructure is state land under the management control of the Indonesian Railways Company or known as P.T. Kereta Api Indonesia (PT. KAI). If the land is not used based on its function, the government will take over to manage the land for development. The effectiveness of this development will have a positive impact in the future, which is better than before. An important issue, in this case, is related to the construction of a station market by the Regency Governments on state land managed by PT. KAI and creates discrepancies with the tenants as third parties. This study used the legal research method to analyze the problems with the black letter law paradigm. Data collection techniques in this study used library research by collecting legal materials. Legal materials were analyzed deductively using interpretation methods (hermeneutics). The results found that it is possible to take legal actions by transferring the fixed assets of PT. KAI in the form of land to the Ponorogo Regency Government. The legal action can later be made based on the agreement between the tenants as a third party, PT. KAI, and the Ponorogo Regency Government. The effectiveness of the construction of the station market can be achieved with the support of all parties, especially the management of the market and merchants as actors in economic activities in the market.